(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides brief information about species on Earth, species composition of Central Asian fauna. Material methods and research methods for the study of bark-eating beetles distributed in the territory of Uzbekistan are presented. A brief analysis of the literature on the study of the topic is provided. Based on the results of the research, a list of the species of bark-eating beetles of Uzbekistan, placed according to their systematic position, is given. The shares of species in the sections of tribes and clans are analyzed in tabular and graphical form.